Penerapan Positive Mind Melalui Self Affirmation Terhadap Perasaan Body Shaming Pada Siswa-Siswi Di MAN 4 Kediri - Andika Siswoaribowo; Diana Rachmania; Dhina Widayati (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
Body shaming is an event experienced by a person when an individual is seen as something that is not good and has deficiencies by someone, especially in terms of body posture. Given the enormous impact it has generated, it is necessary to apply positive thinking as an effort to strengthen understanding of positive self-viewing behavior, one form of which is self-affirmation. The purpose of this community service is to provide health education about the importance of a positive mind through self-affirmation when experiencing body shaming. The population is 30 students, consisting of PMR cadres totaling 6 students, and 24 other student members. PMR cadres are selected students from PMR MAN 4 Kediri who will be empowered. The community service instrument uses an observation sheet. The results of the cadres before the intervention had the ability in the adequate category with a mean of 24. After the intervention was given they had the ability in the good category with a mean of 31.4. The results of PMR members before being given the intervention had abilities in the less category with a mean of 13.2. After being given the intervention, they had sufficient ability with a mean of 24. This means that cadres and other PMR members experienced an increase in the ability score to apply self-affirmation as an effort to avoid feelings of body shaming. The results of the analysis showed that there was an increase in scores before and after the intervention for PMR cadres and members. The application of positive thoughts through self-affirmation is able to help form an acceptance process in a person so that it is believed to be able to minimize negative thoughts as a result of the emergence of feelings of body shaming. We recommend that knowledge about the importance of applying self-affirmation in overcoming feelings of body shaming can be disseminated to all school members as an effort to foster positive thinking and maintain mental health.